Доктринальна концепція модернізації конституційних положень щодо засад конституційного ладу України - Крусян, Анжелика Романовна; Крусян, Анжеліка Романівна; Krusyan, Аnjelika R. (My University, 2013)
The article presents the author's doctrinal concept aimed at modernizing the provisions of Ukrainian Constitution related to the fundamentals of Constitutional order of the state and society in the context of modern Constitutional reform in Ukraine and accounting for Constitutional law theory and practice.
Крусян А. Р. Доктринальна концепція модернізації конституційних положень щодо засад конституційного ладу України / А. Р. Крусян// Юридичний вісник : щоквартальний журнал. - 2013. - № 2. - С. 21-30.
Keywords: конституційні перетворення; конституційна модернізація; Конституція України; конституційний лад; засади конституційного ладу; конституционные преобразования; конституционная модернизация; Конституция Украины; конституционный строй; основы конституционного строя; constitutional reforms; constitutional modernization; The Constitution of Ukraine; constitutional order; the foundations of the constitutional system